The Significance of SKABAPUTRA in the Socio-cultural Space of the Lithuanian-Latvian Borderland - Noreikaitė, Auksė (Acta humanitarica academiae Saulensis, 2021)
The aim of the article is to investigate the significance of the traditional Latvian dish – skabaputra (Latvian skābputra – sour porridge made from barley groats and curdled milk) – in the socio-cultural space of the Lithuanian-Latvian borderland in various periods. The research is based on the empirical material collected by the author in several stages (between 2008 and 2019) in the municipalities of Lithuanian-Latvian borderland. The methods applied in this research were quantitative content analysis, case analysis, interpretative, and comparative methods. Skabaputra can be considered a traditional dish of the Lithuanian-Latvian border region, which was widely established here at the end of the 19th century and was an important part of the dietary culture of Lithuanian Latvians and border Lithuanians until the middle of the 20th century. The history of this dish is closely related to the ethnic and social processes that took place and are still taking place in the Lithuanian-Latvian borderland. Skabaputra came to this border area together with Latvian emigrants as well as with Lithuanians migrating on both sides of the border or Lithuanian re-emigrants from Latvia. The inclusion of this dish in the Lithuanian menu is related to the processes of acculturation and assimilation as well as to social processes – the accumulation of cultural capital in order to achieve a higher social status. At the end of the 19th century – in the middle of the 20th century, the skabaputra performed an important function of an ethnic marker. This dish did not correspond to the dietary habits of some Lithuanians and was used to create nicknames for Latvians. Other Lithuanians also considered skabaputra as a social marker, as for them, eating the dish meant an opportunity to change their status in the social hierarchy. During this period, skabaputra also performed the function of an ethnic link – it helped to consolidate part of the residents of the Lithuanian-Latvian borderland into a single community, and the dish also became a local marker, separating the residents of the border area from the residents of other areas of Lithuania. From the second half of the 20th century, we can record the decline of the skabaputra tradition, which coincided with the assimilation processes of the Latvian ethnic minority, leading to a decrease in the prestige of Latvian culture on the Lithuanian-Latvian border and in the importance of Latvian cultural attributes for social status. In the 2020s of the 21st century, we can observe the “rebirth” and “revival” of the skabaputra, which coincides with the regionalist movement and the construction of local identities taking place on the Lithuanian-Latvian border. Skabaputra becomes an important attribute that supports not only the ethnic identity of Lithuanian Latvians, but generally establishes the distinctiveness of all Lithuanian-Latvian borderland residents. Due to the development of the Lithuanian-Latvian borderland tourism industry, the modern skabaputra claims to once again become an important summer dish of the residents of the border region and an important local and regional marker.